Community Perceptions on Transparency and Accountability In Village Fund Management: A Case Study of Lassang Barat Village, Takalar Regency - Nasrullah, Nasrullah; Muttalib, Abdul; Sabil, Ibnu (Universitas Muhammadiyah Makassar, 2025)
This study analyzes community perceptions of transparency and accountability in the management of Village Fund Allocation (Alokasi Dana Desa/ADD) in Lassang Barat Village, Polombangkeng Utara Subdistrict, Takalar Regency. The Village Fund program is designed to enhance rural welfare and quality of life through participatory governance and accountable financial management. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving village officials, community members, and other relevant stakeholders. The analysis focused on five stages of ADD management: planning, implementation, administration, reporting, and accountability. The findings indicate that in Lassang Barat Village, ADD management is generally perceived positively, as planning and implementation processes involve active community participation and compliance with established procedures. However, challenges persist in other contexts, including limited understanding of accounting principles, weak adherence to regional regulations, and inadequate human resource capacity. These issues reduce the overall effectiveness of ADD management and highlight the need for technical assistance and continuous capacity development. The study concludes that while the ADD program contributes positively to community development, inconsistencies in implementation and regulatory compliance remain. Strengthening capacity building, promoting community engagement, and enhancing monitoring mechanisms are recommended to improve transparency and accountability in village financial governance.